Bootstrap confidence intervals of CNpk for type-II generalized log-logistic distribution - Srinivasa Rao Gadde; K. Rosaiah; SVSVSV Prasad (Journal of Industrial Engineering International, 2019)
This paper deals with construction of confidence intervals for process capability index using bootstrap method (proposed by Chen and Pearn in Qual Reliab Eng Int 13(6):355-360, 1997) by applying simulation technique. It is assumed that the quality characteristic follows type-II generalized log-logistic distribution introduced by Rosaiah et al. in Int J Agric Stat Sci 4(2):283-292, (2008). Discussed different bootstrap confidence intervals for process capability index. Maximum likelihood method is considered for obtaining the estimators of the parameter. Monte Carlo simulation technique is applied to find out the coverage probabilities and average widths of the bootstrap confidence intervals. The results are illustrated with real data sets.
Keywords: 650; Process capability index; Bootstrap confdence interval; Maximum likelihood estimate; Type-II generalized log-logistic distribution